Contestation and Negotiation on Interfaith Inheritance in Pancasila Village - Nur Fadhilah; Muhammad Mufti al Anam; Nuril Farida Maratus (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2024)
This research aims to investigate the division of inheritance between different religions in Kampung Pancasila Balerejo Wlingi Blitar and analyze the relationship between legal systems in the division of inheritance. This research is a non-doctrinal research using a legal pluralism approach. Data were collected through document study, observation, focus group discussion, and in-depth interviews. The data was analyzed using Sally Falk Moore's theory of legal pluralism. The results showed that the division of inheritance was carried out equally between men and women even though family members adhered to different religions. The process of inheritance division is carried out by deliberation by presenting village officials. The reality of the division of inheritance between different religions in Pancasila Village shows that local law and state law run simultaneously and complement each other. Kampung Pancasila has a self-regulating inheritance system. The capacity possessed by the people of Pancasila Village to regulate independently shows the existence of autonomy. However, this autonomy is not absolute (the semi-autonomous social field) due to the influence of state organs. These, namely village officials, come from outside the semi-autonomous area and affect the distribution of inheritance. This research contributes to identifying the contestation and negotiation between legal systems in the inheritance distribution practices of multi-religious families. In addition, this research also contributes to providing alternative solutions to the division of inheritance in multi-religious families.